Влияние природы криопротекторов на размер липосом с арглабином - Тихонова, Е.В.; Смагулов, А.М.; Жанымханова, П.Ж.; Тажбаев, Е.М.; Адекенов, С.М. (Изд-во КарГУ, 2010)
Қатерлі ісікке қарсы əсері бар табиғи арглабинді липосомалар эмульгация əдісімен алынды. Поливинил спиртін — эмульгатор жəне D-лактоза, D-маннит, D-глюкозаны криопротекторлар ретінде қолдану арқылы соя лецитин негізіндегі липосома синтезі үшін оңтайлы жағдай таңдалды. Атомды-күштік сканерлеу микроскопия арқылы липосома өлшемі анықталды. Эмульгация əдісі липосомаларды 50–130 нм диаметр шамасында алуға мүмкіндік берді. Some liposomes with native arglabin having antitumor activity were extracted by the method of emulsification. Optimal conditions for synthesis of liposomes on the basis of soya lecitine with usage of polyvinyl alcohol as emulgator and D-glucose, D-lactose, D-mannit as cryoprotectors were chosen. The size of liposomes was established by mean of scanning atomic-force electronic microscopy. This method allowed to obtain liposomes of 50–130 nm in diameter.
Influence of nature of cryoprotectors on size of liposomes with arglabin
Keywords: лекарственное средство; биодоступность; растворимость; солюбилизатор; кристаллическое состояние; твердая дисперсия; наночастица; арглабин; липосома; криопротектор